2007
DOI: 10.1539/joh.49.431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Topical Exposure to Low‐Dose Noxious Chemicals and Stress on Skin Sensitivity in Mice

Abstract: Effect of Chronic Topical Exposure toLow-Dose Noxious Chemicals and Stress on Skin Sensitivity in Mice: Yumiko NAKANO. Department of Environmental Health, Osaka Prefectural Institute of Public Health-It has been suggested that the recent increase in inflammatory diseases is related to an increase in environmental chemicals and psychiatric stress. To investigate the effect of chronic topical exposure to chemicals and isolation stress, low-dose formalin (a mild contact sensitizer and an irritant), 2,4,6-trinitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, the outcome of corticosterone and epinephrine depends on their concentrations. Using a different contact sensitizing reagent (trinitrochlorobenzene) and isolation stress, Nakano also found that stress enhanced the cutaneous immune response as evaluated by ear swelling [72]. However, stress alone did not enhance the ear swelling response of mice treated with the contact irritant, sodium dodecyl sulfate.…”
Section: Impact Of Psychological Stress On Innate and Adaptive Immmentioning
confidence: 99%
“…Therefore, the outcome of corticosterone and epinephrine depends on their concentrations. Using a different contact sensitizing reagent (trinitrochlorobenzene) and isolation stress, Nakano also found that stress enhanced the cutaneous immune response as evaluated by ear swelling [72]. However, stress alone did not enhance the ear swelling response of mice treated with the contact irritant, sodium dodecyl sulfate.…”
Section: Impact Of Psychological Stress On Innate and Adaptive Immmentioning
confidence: 99%
“…In fact, ACD accounts for one of the highest rates of work-related skin disease (Karsak et al, 2007;Martin, 2012), and work-associated exacerbation of skin sensitivity is increasing in developed countries (Nakano, 2007). Contact hypersensitivity (CHS) is a model of this allergic response.…”
Section: Introductionmentioning
confidence: 99%
“…First: elevated temperatures increase the solubility of PAHs and other lipophiles in water and also increase the vaporization of these species and hence result in higher air concentrations [271]. Second: elevated environmental temperatures accelerate the absorption of toxicants through respiratory, cutaneous and gastrointestinal routes and hence increase toxicity [210,[271][272][273]. Third; elevated temperatures increase thermal stress, impair heat stress response and delay unfolded protein recovery [274][275][276].…”
Section: Global Warmingmentioning
confidence: 99%